Sensitive detection of pre-integration intermediates of LTR retrotransposons in crop plants - Cho, Jungnam (Nat Plants, 2018)
Retrotransposons have played an important role in the evolution of host genomes1,2. Their impact is mainly deduced from the composition of DNA sequences that have been fixed over evolutionary time 2. Such studies provide important “snapshots” reflecting the historical activities of transposons but do not predict current transposition potential. We previously reported Sequence-Independent Retrotransposon Trapping (SIRT) as a method that, by identification of extrachromosomal linear DNA (eclDNA), revealed the presence of active LTR retrotransposons in Arabidopsis3. However, SIRT cannot be applied to large and transposon-rich genomes, as found in crop plants. We have developed an alternative approach named ALE-seq (amplification of LTR of eclDNAs followed by sequencing) for such situations. ALE-seq reveals sequences of 5’ LTRs of eclDNAs after two-step amplification: in vitro transcription and subsequent reverse transcription. Using ALE-seq in rice, we detected eclDNAs for a novel Copia family LTR retrotransposon, Go-on, which is activated by heat stress. Sequencing of rice accessions revealed that Go-on has preferentially accumulated in indica rice grown at higher temperatures. Furthermore, ALE-seq applied to tomato fruits identified a developmentally regulated Gypsy family of retrotransposons. A bioinformatic pipeline adapted for ALE-seq data analyses is used for the direct and reference-free annotation of new, active retroelements. This pipeline allows assessment of LTR retrotransposon activities in organisms for which genomic sequences and/or reference genomes are either unavailable or of low quality.